2005
DOI: 10.1021/cm048993d
|View full text |Cite
|
Sign up to set email alerts
|

Low-k Interlayer Dielectric Materials:  Synthesis and Properties of Alkoxy-Functional Silsesquioxanes

Abstract: Two new types of silsesquioxanes, (HSiO 3/2 ) x [( t BuO)SiO 3/2 ] z or T H Q and (HSiO 3/2 ) x (RSiO 3/2 ) y [( t BuO)SiO 3/2 ] z or T H T R Q (R ) octadecyl), were synthesized and studied as low-k dielectric materials for electronic applications. The materials were prepared by cohydrolysis and condensation of alkoxy monomers, (AcO) 2 Si(O t Bu) 2 , HSi(OEt) 3 , and CH 3 (CH 2 ) 17 Si(OMe) 3 . Spectroscopic data supported retention of tertiary alkoxy groups [( t BuO)SiO 3/2 or ( t BuO) 2 SiO 2/2 ] and presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…The 29 Si{ 1 H} CP MAS NMR spectrum exhibits several resonances in the range of −130 to +10 ppm that were simulated with five Gaussian peaks with δ iso at −72, −60, −46, −21 and 3 ppm. These fives coordination environments correspond to PhSi(NCN) 3 , HSi(NCN) 3 , HPhSi(NCN) 2 , HPhSiCl(NCN) and (Me) 3 Si(NCN) groups, respectively …”
Section: Resultsmentioning
confidence: 99%
“…The 29 Si{ 1 H} CP MAS NMR spectrum exhibits several resonances in the range of −130 to +10 ppm that were simulated with five Gaussian peaks with δ iso at −72, −60, −46, −21 and 3 ppm. These fives coordination environments correspond to PhSi(NCN) 3 , HSi(NCN) 3 , HPhSi(NCN) 2 , HPhSiCl(NCN) and (Me) 3 Si(NCN) groups, respectively …”
Section: Resultsmentioning
confidence: 99%
“…CPMES showed much higher thermal stability than Me-H-T due to the self-crosslinking by the epoxide group. However, the majority of studies with polysilsesquioxanes have been conducted in the thin film state through the spin coating technique on top of silicon substrates [30,31] and no free-standing, ladder-like PSSQ film formation was reported so far. Free-standing membranes provide an excellent opportunity to investigate the unique properties of the film by eliminating additional effects due to the presence of a mechanical support.…”
Section: Introductionmentioning
confidence: 99%
“…Semifluorinated polymers are possible candidates for interlayer dielectric materials (ILD) and also considered as good materials for membrane-based separation. [14][15][16][17] Korshak and coworker reported that the polymer chain having cyclic side cardo group (for example; fluorene, phthalide, or phthalimidine) would increase in both glass transition temperature and thermo-oxidative stability and also good solubility. 18 Because of all these interesting properties of fluorinated polymers a considerable attention has been devoted to the preparation of new class of fluorine containing polymers or improvement of the properties of the existing polymers by judicious selection of new monomers.…”
Section: Introductionmentioning
confidence: 99%